'The Inexhaustible Surface of Things': Stefano Tamburini's Comic Book Work. Issue 1 (1st March 2020) - Castaldi, Simone
Abstract: This article explores the work of Stefano Tamburini (1955–1986) in relationship to the 'high arts' in the 1980s. By concentrating on Tamburini's least known works (to this day, among his many works, only the RanXerox saga is actually available for English-speaking readers), it is possible to regard his art as a bridge tying comics with the aesthetic and theoretical preoccupations of many of the leading artists of the postmodern trans-avant-garde of the late-1970s and early-1980s in Italy. This article demonstrates how Tamburini offered a model of comics in dialogue with the rest of the contemporary art world, often taking the lead and generating fruitful exchanges both with the field of literature and the visual arts.